Psychological Capital as a Predictor of Innovative Work Behavior in Employees of PT. Victory International Futures Yogyakarta - Asshiddiqie, Thoriq; Endang Kusmaryani, Rosita; Mukta, Mst. Najmeen (Green Publisher Indonesia, 2024)
Innovative ideas should ideally originate from individuals. Innovation often stems from organizational initiatives, resulting in not all employees being able to generate and apply their creative ideas. This research utilized a quantitative ex-post facto research method. The study was conducted on employees of PT. Victory International Futures Yogyakarta, with a sample size of 55 employees. Sample selection was based on the Krejcie and Morgan table. Data collection employed psychological scales using Likert scales. The data collection instruments included the Innovative Work Behavior scale modified from Janssen and the Psychological Capital Questionnaire (PCQ-24) modified from Luthans et al. Validity was assessed using the Gregory test and reliability was calculated using Cronbach's Alpha. The findings of this study indicated that psychological capital had a influence on innovative work behavior. Partially, the study demonstrated that the hope dimension of psychological capital influenced on innovative work behavior, the efficacy dimension of psychological capital also influenced on innovative work behavior, while the resilience dimension of psychological capital did not show a influence on innovative work behavior, and the optimism dimension of psychological capital did not show a influence on innovative work behavior.